Analisis Perubahan Tutupan Lahan Pada Tahun 2013 dan 2024 Menggunakan Citra Landsat 8 di Kota Jambi - Simarmata, Agustina Rida; Achmad, Eva; Harmes, Harmes (Universitas Batanghari Jambi, 2025)
This research aims to analyze land cover changes in 2013 and 2024 using Landsat 8 imagery in Jambi City. The analysis was conducted using the supervised classification method with the Maximum Likelihood Classification (MLC) algorithm, followed by an accuracy assessment. The accuracy assessment was carried out to evaluate the consistency between the land cover classification results derived from the Landsat imagery and the land cover observed in Google Earth Pro. The results show that land cover changes in Jambi City between 2013 and 2024 reveal significant conversions of vegetated land, primarily into built-up areas covering 1,780.69 hectares (10.50%) and, to a smaller extent, into water bodies (24.65 hectares or 0.15%) and open land (88.35 hectares or 0.52%). Open land predominantly transitioned into built-up areas (326.68 hectares or 1.93%), while water bodies experienced the least change but still showed some conversion into built-up areas (23.04 hectares or 0.14%). Overall, there has been an increase in built-up areas, indicating rapid urban development, while vegetated land has decreased, reflecting the pressures of urbanization and land-use changes.